Design and optimisation of a fuzzy-PI controlled modified inverter-based PMSM drive employed in a light weight electric vehicle - Sain C.; Banerjee A.; Biswas P.K.; Azar A.T.; Babu T.S. (Inderscience Publishers, 2023)
Computer circuits; Controllers; DC-DC converters; Electric drives; Electric inverters; Electric machine control; Electric vehicles; Fuzzy control; Fuzzy logic; Particle swarm optimization (PSO); Pulse width modulation; Stochastic systems; Synchronous motors; Traction motors; Traffic signals; Voltage control; FLC; Fuzzy logic controllers; Optimisations; Permanent Magnet Synchronous Motor; Pulsewidth modulations (PWM); Permanent magnets